A Peculiar Fate : Metaphysics and World-History in Kant - Fenves, Peter (Cornell University Press, 2019)
Peter Fenves here investigates Kant's ongoing effort to bring metaphysical and strictly historical concepts of the world together in his presentation of world-history. Fenves argues that, far from being a mere illustration of his metaphysical principles, Kant's attempt to present history in its entirety played a vital role in the transformation of his concept of philosophy. A Peculiar Fate demonstrates for the first time how Kant's concern with history motivates and gives shape to his "discovery" that a systematic philosophical inquiry must rest on human freedom.